Baleczky Emil és az ukrán nyelvemlékek - Kocsis Mihály (II. RF KMF-„RIK-U” Kft., 2020)
A Magyarországhoz kötődő ukrán nyelvemlékeknek Baleczky Emil három tanulmányt is szentelt, egyet társszerzőként. Ezekben az 1666. évi zborói szerződést (Балецкий 1956), a XVII–XVIII. század fordulóján keletkezett egri irmologiont (Балецкий 1958) és Báthory Zsófia 1674-ből származó oklevelét (Перени–Балецкий 1959) elemzi. Mind a három írás a Magyar Tudományos Akadémia szlavisztikai folyóiratában, a Studia Slavicában jelent meg.

Abstract. The article deals with three essays written by Emil Baleczky that are dedicated to Ukrainian linguistic records kept in Hungary. All these manuscripts were written in the North-Eastern territory of the Hungarian Kingdom in the 17th and 18th centuries. As a consequence, the studies in question can still be regarded of crucial importance in the research of the history of the Subcarpathian Ukrainian dialects.
https://kmf.uz.ua/wp-content/uploads/2020/11/final-baleczky_kotet_2020-10-28.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008462
Keywords: Baleczky Emil; 1666. évi zborói szerződés; egri irmologion; Báthory Zsófia 1674. évi oklevele